The effect of treatment duration on the prognosis of adhd: a multi-center naturalistic follow-up study - Ercan, Eyuep Sabri; Bilgic, Ayhan; Tufan, Ali Evren; Akca, Omer Faruk; Yazici, Ipek Percinel; Bilac, Oznur; Ozyurek, Suleyman Emre (Elsevier Ireland Ltd, 2025)
Objective: This study aimed to evaluate the effect of medication duration over a 5-year period on the prognosis of Attention-Deficit/ Hyperactivity Disorder (ADHD) and the accompanying disruptive behavioral symptoms using a naturalistic methodology. Methods: The sample comprised 576 ADHD cases referred to 16 Child and Adolescent Psychiatry Clinics in 13 cities in T & uuml;rkiye, aged between 7-12 five years ago and 12-18 currently. Baseline and current Turgay DSM-IV Disruptive Behavior Disorders Rating Scale (T-DSM-IV-S) scores completed by parents were compared. Sociodemographic data, treatment processes, life events, and habits were recorded. Disorder severity and recovery levels were determined using the Clinical Global Impression Scale (CGI). Results: All current T-DSM-IV-S scores were significantly lower than the baseline scores. Longer duration of medication use, receiving psychotherapy, and higher socioeconomic status were associated with better CGI scores in the present study. However, increased baseline conduct disorder symptoms, being bullied, longer duration of Internet usage, dropping out of school, smoking, and older age were associated with worse CGI scores. Conclusion: Our study indicates that a longer duration of medication use is associated with better global improvement in children with ADHD. Better identification of the factors that may directly or indirectly affect the general improvement in ADHD cases and changing these factors may enable a more positive prognosis.
Keywords: ADHD; Medication; Treatment duration; Prognosis; Clinical outcomes